1984
DOI: 10.1161/01.res.54.2.173
|View full text |Cite
|
Sign up to set email alerts
|

Pericardial influences on ventricular filling in the conscious dog. An analysis based on pericardial pressure.

Abstract: SUMMARY. Twenty-five dogs were chronically instrumented to investigate the effects of the normal pericardium on cardiac function. Pulse-transit ultrasonic transducers were implanted to measure multiple ventricular dimensions. The pericardium was incised transversely at the base of the heart and precisely reapproximated, so as to disturb its characteristics minimally. One week later, the dogs were studied in the conscious state, and left ventricular, right ventricular, pericardial, and pleural pressures were me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
16
0
3

Year Published

1985
1985
2013
2013

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 57 publications
(19 citation statements)
references
References 39 publications
(34 reference statements)
0
16
0
3
Order By: Relevance
“…This procedure allowed us to remove the heart gently while leaving most of the pericardial sac intact. After instrumenting the heart (as described below), we popped it back into the pericardial sac and loosely sutured the incision from its inferior margin to the level of the inferior border of the great vessels (Tyson et al, 1984).…”
Section: Methods Preparationmentioning
confidence: 99%
“…This procedure allowed us to remove the heart gently while leaving most of the pericardial sac intact. After instrumenting the heart (as described below), we popped it back into the pericardial sac and loosely sutured the incision from its inferior margin to the level of the inferior border of the great vessels (Tyson et al, 1984).…”
Section: Methods Preparationmentioning
confidence: 99%
“…Based on these concepts and direct measurement of pericardial surface pressure with flat balloons, it has been variously suggested that right heart pressure equals3' 4 or nearly equals intrapericardial surface pressure.3 '5 However, if right heart pressure equals the pericardial surface pressure, then the right heart transmural pressure must be zero. From results presented in several earlier reports, one can infer that this is not the case; that is, there seems to be a nonzero transmural right heart pressure.6 10 Unfortunately, none of these experi-ments was designed specifically to test the equality of right heart and pericardial pressures and all of them can be faulted in some way when interpreted in this manner. Nonetheless, this discrepancy suggests the need for a well-controlled experiment designed specifically to test the hypothesis that right heart and pericardial surface pressures are equal.…”
mentioning
confidence: 99%
“…early in diastole occurred in the acutely dilated left ventri cle with elevated filling pressures which was induced by microsphere embolization of the left main coronary ar tery and that this redistribution was mediated by pericar dial restraint. Because the pericardial restraining effects predominantly influence the right ventricular filling [20], redistribution of diastolic filling to early in diastole is con sidered to occur much more easily in the right ventricle. Thus, an increased E and a decreased A/E noted in the patients with acute right ventricular infarction would be explained by the pericardial restraint.…”
Section: Controlmentioning
confidence: 99%